Reconsidering the orphan problem: the emergence of male caregivers in Lesotho. (25th July 2016) - Block, Ellen
ABSTRACT: Care for AIDS orphans in southern Africa is frequently characterized as a "crisis", where kin-based networks of care are thought to be on the edge of collapse. Yet these care networks, though strained by AIDS, are still the primary mechanisms for orphan care, in large part because of the essential role grandmothers play in responding to the needs of orphans. Ongoing demographic shifts as a result of HIV/AIDS and an increasingly feminized labor market continue to disrupt and alter networks of care for orphans and vulnerable children. This paper examines the emergence of a small but growing number of male caregivers who are responding to the needs of the extended family. While these men are still few in number, the strength of gendered ideologies of female care means that this group of men is socially, if not statistically significant. Men continue to be considered caregivers of last resort, but their care will close a small but growing gap that threatens to undermine kin-based networks of care in Lesotho and across the region. The adaptation of gender roles reinforces the strength and resilience of kinship networks even when working against deeply entrenched ideas about gendered division of domestic labor.